2017
DOI: 10.1037/xhp0000426
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale horizontal-vertical illusion produced with small objects separated in depth.

Abstract: Two experiments (total N = 81) we conducted to investigate the basis for the large-scale horizontal-vertical illusion (HVI), which is typically measured as 15–20% and has previously been linked to the presence of a ground plane. In a preliminary experiment, vertical rods of similar angular extents that were either large (4.5–7.5 m) and far, or small (0.9–1.5 m) and near, were matched to horizontal extents in a virtual environment by adjustment of horizontal gaps or rods. Large/far objects showed a larger HVI (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Regardless of the mechanism, the horizontal‐vertical illusion has been demonstrated for buildings in real environments as well as pictures and virtual‐reality versions of them (e.g., Yang et al, 1999); however, the magnitude of this illusion generally depends on the size of the object. Specifically, for large objects like buildings, the effect of the horizontal‐vertical illusion is much greater (~20%) than for small objects (~5%; see Chapanis & Mankin, 1967; Higashiyama, 1992; see Li & Durgin, 2017 for medium‐sized objects). Moreover, when observing large objects, the horizontal‐vertical illusion is independent of observer orientation but the effect is retinotopic when viewing smaller objects (Klein et al, 2016).…”
mentioning
confidence: 99%
“…Regardless of the mechanism, the horizontal‐vertical illusion has been demonstrated for buildings in real environments as well as pictures and virtual‐reality versions of them (e.g., Yang et al, 1999); however, the magnitude of this illusion generally depends on the size of the object. Specifically, for large objects like buildings, the effect of the horizontal‐vertical illusion is much greater (~20%) than for small objects (~5%; see Chapanis & Mankin, 1967; Higashiyama, 1992; see Li & Durgin, 2017 for medium‐sized objects). Moreover, when observing large objects, the horizontal‐vertical illusion is independent of observer orientation but the effect is retinotopic when viewing smaller objects (Klein et al, 2016).…”
mentioning
confidence: 99%
“…The present study therefore seeks to investigate the estimation of angular declination in the presence or absence of a ground plane. It has recently been observed that explicit judgments of azimuthal direction are larger in the presence of a ground plane ( Durgin & Keezing, 2018 ), and that horizontal–vertical illusions are larger for objects separated in depth on a ground plane ( Li & Durgin, 2017 ). The present investigations were carried out to better understand the possible effects of the ground plane on explicit estimates of angular declination.…”
mentioning
confidence: 99%
“…The difference between the current research and previous experiments is not entirely due to task differences, since we did not directly compare the difference between the verbal and nonverbal paradigms in one study. We directly adopted a nonverbal paradigm, like most distance studies in the recent literature 31 , 39 , 40 . Other differences may also play a role.…”
Section: Discussionmentioning
confidence: 99%